3D printing: Challenges and opportunities of an emerging disruptive technology - Co, Joseph Rei Mark (Animo Repository, 2019)
According to the 2018 Global Competitiveness Index (GCI) report of the World Economic Forum, the Philippines moved 12 places landing 56th out of 140 countries based on different metrics on competitiveness such as the business dynamism, infrastructure, and ICT adoption. In order to continue this positive trend and remain competitive, the Philippines has to remain steadfast and welcoming of technological changes that would drive the economy for Industry 4.0. Among these disruptive technological advancements is 3D printing. At present, the local 3D printing industry is limited due to the barriers of adoption such as: (1) high cost, (2) limited build size, (3) lack of skilled workforce, (4) lack of regulations, and (5) potential security risks. Nevertheless, 3D printing technology offers many advantages particularly: (1) freedom of design leading to mass customization, (2) speed and adaptability, and (3) sustainability which are key drivers for the adoption of the technology. It is therefore imperative that the Philippines capitalize on these opportunities and address the deficiencies in order to harness the full potential of 3D printing. © 2019 IEEE